Survival patterns of Dekkera bruxellensis in wines and inhibitory effect of sulphur dioxide - Malfeito-Ferreira, Manuel (2009)
The wine spoilage yeast species Dekkera bruxellensis, after inoculation in red wines, displayed three survival patterns characterized by: i) initial lag phase followed by growth and sequential death; ii) initial death phase leading to reduced viable counts followed by growth and sequential death; and iii) death phase leading to complete loss of viability. These survival patterns were observed for the same strain in different dry red wine blends with 12% (v/v) ethanol and pH 3.50, in the absence of free sulphur dioxide. For the same wine blend, these patterns also varied with the tested strain. Under laboratory conditions the addition of 150 mg/l of potassium metabisulphite (PMB) to dry red wine with 12% (v/v) ethanol and pH 3.50 reduced initial cell counts by more than 6 logarithmic cycles, inducing full death within less than 24 h. Winery trials showed that D. bruxellensis blooms were only prevented in the presence of about 40 mg/l of free sulphur dioxide in dry red wine, with 13.8% (v/v) ethanol and pH 3.42, matured in oak barrels. These different amounts of PMB and sulphur dioxide corresponded to about 1 mg/l of molecular sulphur dioxide. Our results therefore demonstrate that the control of populations of D. bruxellensis growing in red wine can only be achieved under the presence of relatively high doses of molecular sulphur dioxide.